Climate effects on nesting phenology in Nebraska turtles. Issue 3 (8th January 2021) - Hedrick, Ashley R.; Greene, Daniel U.; Lewis, Erin L.; Hood, Andrew S.; Iverson, John B.
Abstract: A frequent response of organisms to climate change is altering the timing of reproduction, and advancement of reproductive timing has been a common reaction to warming temperatures in temperate regions. We tested whether this pattern applied to two common North American turtle species over the past three decades in Nebraska, USA. The timing of nesting (either first date or average date) of the Common Snapping Turtle ( Chelydra serpentina ) was negatively correlated with mean December maximum temperatures of the preceding year and mean May minimum and maximum temperatures in the nesting year and positively correlated with precipitation in July of the previous year. Increased temperatures during the late winter and spring likely permit earlier emergence from hibernation, increased metabolic rates and feeding opportunities, and accelerated vitellogenesis, ovulation, and egg shelling, all of which could drive earlier nesting. However, for the Painted Turtle ( Chrysemys picta ), the timing of nesting was positively correlated with mean minimum temperatures in September, October, December of the previous year, February of the nesting year, and April precipitation. These results suggest warmer fall, and winter temperature may impose an increased metabolic cost to painted turtles that impedes fall vitellogenesis, and April rains may slow the completion of vitellogenesis through decreased basking opportunities. For both species, nest deposition was highly correlated with body size, and larger females nested earlier in the season. Although average annual ambient temperatures have increased over the last four decades of our overall fieldwork at our study site, spring temperatures have not yet increased, and hence, nesting phenology has not advanced at our site for Chelydra . While Chrysemys exhibited a weak trend toward later nesting, this response was likely due to increased recruitment of smaller females into the population due to nest protection and predator control ( Procyon lotor ) in the early 2000s. Should climate change result in an increase in spring temperatures, nesting phenology would presumably respond accordingly, conditional on body size variation within these populations. Abstract : A frequent response of organisms to climate change is altering the timing of reproduction. Over the past three decades, the timing of nesting of the Common Snapping Turtle ( Chelydra serpentina ) was negatively correlated with mean December maximum temperatures of the preceding year and mean May minimum and maximum temperatures in the nesting year and positively correlated with precipitation in July of the previous year. For the Painted Turtle ( Chrysemys picta ), the timing of nesting was positively correlated with mean minimum temperatures in September, October, December of the previous year, February of the nesting year, and April precipitation.